2019
DOI: 10.5430/jnep.v9n10p59
|View full text |Cite
|
Sign up to set email alerts
|

Infection prevention and control curriculum in undergraduate nursing program: Internship nursing students’ perspectives

Abstract: Undergraduate nursing education plays a vital role in acquiring the necessary competency for patient safety. Infection prevention and control is a very critical topic for providing patient safety so, undergraduate and graduate nursing students should be competent in infection prevention and control. The aim of this study was to measure the undergraduate nursing program effectiveness in improving knowledge and practice of infection prevention and control of internship nursing students and to identify their lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…Interestingly, clinician self-evaluations and patient evaluations of clinician performance did not always align to that of IPC experts, and this was particularly true for procedures involving PPE, which were poorly performed. Poor knowledge pertaining to correct use of the N95 respiratory mask and other PPE equipment was also a finding in the study of nurses by Abdelaziz et al 21 The present study additionally revealed that clinician confidence in providing and being audited for, best IPC practice, and patients' confidence in receiving best IPC care, was positively associated with clinician experience. TIs, whose confidence in IPC practice was not matched by the same desire for monitoring or feedback compared with senior colleagues, were the exception, perhaps reflecting some underlying uncertainty regarding their true level of competence.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Interestingly, clinician self-evaluations and patient evaluations of clinician performance did not always align to that of IPC experts, and this was particularly true for procedures involving PPE, which were poorly performed. Poor knowledge pertaining to correct use of the N95 respiratory mask and other PPE equipment was also a finding in the study of nurses by Abdelaziz et al 21 The present study additionally revealed that clinician confidence in providing and being audited for, best IPC practice, and patients' confidence in receiving best IPC care, was positively associated with clinician experience. TIs, whose confidence in IPC practice was not matched by the same desire for monitoring or feedback compared with senior colleagues, were the exception, perhaps reflecting some underlying uncertainty regarding their true level of competence.…”
Section: Discussionsupporting
confidence: 83%
“…Assessment of IPC-related material, both theoretical and practical, could also be enhanced in the final years of training and perhaps routinely incorporated into high stakes/summative assessments. These suggestions echo those of Abdelaziz et al 21 in their 2018 study of IPC in undergraduate nursing curricula, where they identified similar gaps. Mastery of a procedural skill should not assume mastery of the associated IPC techniques used when performing the skill.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…While not yet qualified, nursing students have also been rendering care to patients infected with SARS-CoV-2 and faced with rapid changes in the clinical settings (Taylor et al 2020). Though infection prevention and control are core parts of nurse training (Abdelaziz, Dogham & Elcokany 2019), the novel nature of the pandemic, the high level of Original Research http://www.hsag.co.za Open Access transmissibility of the virus (Di Gennaro et al 2020) and the move to online teaching and learning (SA Government 2020) have resulted in additional challenges for nursing students already under pressure to complete their degrees. This has resulted in increased anxiety impacting academic functioning (Cao et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…HAI-PC knowledge was highlighted as crucial in preparing students to prevent infections during clinical practice, ensuring patient safety, and reducing HAIs [31]. The study by Abdelaziz et al (2019) mentioned the necessity of HAI-PC education in the nursing curriculum and the professional nursing career. Still, the result of the study identified that almost 50% of the students had poor clinical practice skills, and more than 50% had poor knowledge of HAI-PC, along with non-relevant and specific training in the curriculum [32].…”
Section: Discussionmentioning
confidence: 99%